Zebrafish as a Smart Model to Understand Regeneration After Heart Injury: How Fish Could Help Humans - Beffagna, Giorgia (Frontiers in Cardiovascular Medicine, 2019)
Myocardial infarction (MI) in humans is a common cause of cardiac injury and results in irreversible loss of myocardial cells and formation of fibrotic scar tissue. This fibrotic tissue preserves the integrity of the ventricular wall but undermines pump function, leading to congestive heart failure. Unfortunately, the mammalian heart is unable to replace cardiomyocytes, so the life expectancy for patients after an episode of MI is lower than for most common types of cancers. Whereas humans cannot efficiently regenerate their heart after injury, the teleost zebrafish have the capability to repair a ‘broken’ heart. The zebrafish is probably one of the most important models for developmental and regenerative biology of the heart. In the last decades, the zebrafish has become increasingly important for scientific research: it has many characteristics that make it a smart model for studying human disease. Moreover, adult zebrafish efficiently regenerate their hearts following different forms of injury. Due to these characteristics and to the availability of genetic approaches and biosensor zebrafish lines, it has been established useful for studying molecular mechanisms of heart regeneration. Regeneration of cardiomyocytes in zebrafish is not based on stem cells or transdifferentiation of other cells but on the proliferation of preexisting cardiomyocytes. For this reason, future studies into the zebrafish cardiac regenerative mechanisms could identify specific molecules able to regulate the proliferation of preexisting cardiomyocytes; these factors may be studied in order to understand regulation of myocardial plasticity in cardiac repair processes after injury and, in particular, after MI in humans.